2005
DOI: 10.1115/1.2148977
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on a Hybrid Desiccant Dehumidification and Air Conditioning System

Abstract: This paper presents the experimental tests on hybrid desiccant dehumidification and air conditioning systems. Experimental tests are carried out with LiCl desiccant at typical operative ranges for air conditioning applications, particularly for high humid regions like Hong Kong. Results are reported in terms of coefficient of performance (COP) based on primary energy usage and electrical energy usage, respectively. Experiments have demonstrated consistent reduction in humidity ratio satisfying the sensible as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Fig. 5 shows a comparison between the simulated results obtained in the current study and the experimental results obtained by Yong et al [5]. It has been observed that system performance in terms of COP increases with the increase in regeneration temperature.…”
Section: Page 8 Of 43mentioning
confidence: 55%
See 2 more Smart Citations
“…Fig. 5 shows a comparison between the simulated results obtained in the current study and the experimental results obtained by Yong et al [5]. It has been observed that system performance in terms of COP increases with the increase in regeneration temperature.…”
Section: Page 8 Of 43mentioning
confidence: 55%
“…Desiccant cooling was suggested as supplement to conventional vapor compression cooling or evaporative cooling due to its energy and cost saving in hot and humid environment conditions [4]. Experimental tests on hybrid desiccant dehumidification and air conditioning system have been conducted [5] for Hong Kong, a high humid region. It has been evaluated that the hybrid solid desiccant cooling system achieves a higher part load performance in hot and humid climates.…”
Section: Page 2 Of 43mentioning
confidence: 99%
See 1 more Smart Citation
“…Desiccant cooling systems were studied experimentally and theoretically by several researchers. In these studies, it was shown that desiccant cooling systems is suitable for hot and humid environment conditions [4][5][6]. Desiccant air-conditioning systems do not use harmful to the environment refrigerants, neither do they consume electrical energy for the cooling process, but thermal energy, in temperature levels that favor the use of solar energy, and more specifically flat plate solar collectors [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their benefits are meaningful when they interact with renewable energy technologies, such as solar collectors [37,38]. They also reduce moisture from the indoor air and enhance its quality [39][40][41]. For instance, liquid desiccant dehumidification solar systems are used to supply fresh air in humid climate locations using the calcium chloride liquid and a flat-plate solar collector (having an area of 86.16 m 2 ).…”
Section: Solar Desiccant Systemsmentioning
confidence: 99%